Exploring the perceptions of psychiatric patients regarding marijuana use - Leepile A. Sehularo; Emmerentia du Plessis; Belinda Scrooby (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2012)
There is limited understanding on marijuana use by psychiatric patients, specifically with regard as to why they continue to smoke marijuana despite the negative consequences, such as readmittance to psychiatric hospitals following marijuana-induced psychosis. It is, therefore, important to understand why psychiatric patients continue to use marijuana, despite experiencing its negative effects. The purpose of this study was to explore and describe the perceptions of psychiatric patients with regard to marijuana use in Potchefstroom, North West Province, as well as to formulate recommendations for nursing education, nursing research and nursing practice, with the aim of reducing the readmission of psychiatric patients following marijuana-induced psychosis. A qualitative, exploratory, descriptive and contextual research design was followed in order to give ‘voice’ to the perceptions of psychiatric patients about marijuana use. Purposive sampling was utilised to identify participants who complied with selection criteria. The sample size was determined by data saturation, which was reached after 10 individual interviews with psychiatric patients. Unstructured individual interviews were utilised to gather data after written approval from the Ethics committee of the North-West University (Potchefstroom Campus), North West Provincial Department of Health, the clinical manager of the psychiatric hospital where data were collected, as well as from the psychiatric patients. The co-coder and the researcher analysed the data independently. The findings of this study include perceptions of psychiatric patients on the use of marijuana, the negative effects of marijuana use, marijuana use and mental illness, and quitting marijuana. Recommendations were formulated for nursing education, nursing research as well as for nursing practice. Opsomming